mTORC1 inhibitors: is temsirolimus in renal cancer telling us how they really work? - Le Tourneau, C (Nature Publishing Group, 2008)
The proof of principle that a drug targeting mTOR can improve survival has been obtained recently from a large randomised trial using temsirolimus as a first-line therapy in patients with advanced poor prognostic renal cell carcinoma. Consistent data have recently shown the important role of the PI3K/AKT/mTOR signalling pathway in the regulation of crucial metabolic and mitotic functions of cancer cells and endothelial cells allowing a better understanding of the role of mTOR in controlling cancer cell proliferation and survival as well as tumour angiogenesis. As a result, rapamycin derivatives (rapalogues) that block mTOR/Raptor complex 1 were shown to exert direct antiproliferative effects against endometrial cancers, in which cancer cells frequently lose PTEN function as well as mantle cell lymphomas, in which cancer cell proliferation appears to be driven primarily by cyclin D1 overexpression. The overall antitumour effects of rapalogues in renal cell carcinoma appear to be more complex with tumour growth inhibition resulting from direct G1/S cell cycle blockage and/or apoptotic effects in carcinoma cells along with the inhibition of downstream signalling of the HIF1α-induced VEGF/VEGFR autocrine loop in endothelial cells shutting down the maintenance of tumour angiogenesis. Despite extensive cognitive researches, it is difficult to appraise which of those mechanisms is predominant in patients. This review focuses on mechanisms of action of rapalogues focusing on antitumour effects in patients with renal cell carcinoma.